PEMBERDAYAAN MASYARAKAT BERBASIS MASJID UNTUK MENANGKAL RADIKALISME ISLAM DI BANTEN - Muhammad Syafar (Lembaran Masyarakat: Jurnal Pengembangan Masyarakat Islam, 2018)
This paper aims to explore the paradigm of community development within Islamic community and its contribution to prevent radicalism in Indonesia, especially in Banten. Potentially, community empowerment based masque in Banten could be accordance with social culture of Banten Islamic community, which is implemented by 3 (three) approach of social welfare: social philantrophy, social administration and social work. In this paper, community empowerment oriented not only to improve Islamic values but also improving social economy of jama’ah which is participated through strengthening DKM institution, social capital community, entrepreneurship and social defense to prevent radicalism in the framework of Islamic comprehension and its impact on local community. Keywords: Community developmet paradigm, social welfare, community.